Differences in Diet Between Six Neighbouring Groups of Vervet Monkeys. (1st March 2014) - Tournier, Emilie; Tournier, Virginia; van de, Erica; Barrett, Alan; Brown, Leslie; Bshary, Redouan; Schneider, J.
Abstract The comparative approach provides a powerful tool to study evolutionary questions on both intra‐ and interspecific variation. It has been applied to a great variety of taxa, including primates. Primate studies differ from those on most other taxa in two ways: first, data from most study sites contain information about only one group. Second, primatologists have used the comparative approach also to identify local traditions, that is, behaviours that spread through social learning. Here, we evaluate the appropriateness of such data by comparing the diet composition of six neighbouring groups of vervet monkeys, Cercopithecus aethiops. We used scan samples to collect diet data, and abundance measures and phenology to assess the availability of the 14 most important tree species utilised during the study. We calculated indices of diet overlap, which were highly variable and could be remarkably low. Furthermore, we found significant differences between group diets with respect to the relative utilisation of 13 of the 14 tree species. For all 13 species, we found positive correlations between local abundance and appearance in the diet, consistent with the importance of local ecology for diet composition. Nevertheless, more detailed comparisons of pairs of groups often revealed significant mismatches between the relative importance of a tree species and its local abundance. In conclusion, local variation merits increased attention by primatologists. While our results are compatible with the possibility that traditions exist on a local (group) rather than population scale, alternative explanations have to be considered.